Hypomethylation and expression of BEX2, IGSF4 and TIMP3 indicative of MLL translocations in Acute Myeloid Leukemia - Roehrs, Sonja; Dirks, Wilhelm G.; Meyer, Claus; Marschalek, Rolf; Scherr, Michaela; Slany, Robert; Wallace, Andrew; Drexler, Hans G.; Quentmeier, Hilmar (Molecular Cancer, 2009)
Background: Translocations of the Mixed Lineage Leukemia (MLL) gene occur in a subset (5%) of acute myeloid leukemias (AML), and in mixed phenotype acute leukemias in infancy - a disease with extremely poor prognosis. Animal model systems show that MLL gain of function mutations may contribute to leukemogenesis. Wild-type (wt) MLL possesses histone methyltransferase activity and functions at the level of chromatin organization by affecting the expression of specific target genes. While numerous MLL fusion proteins exert a diverse array of functions, they ultimately serve to induce transcription of specific genes. Hence, acute lymphoblastic leukemias (ALL) with MLL mutations (MLLmu) exhibit characteristic gene expression profiles including high-level expression of HOXA cluster genes. Here, we aimed to relate MLL mutational status and tumor suppressor gene (TSG) methylation/expression in acute leukemia cell lines. Results: Using MS-MLPA (methylation-specific multiplex ligation-dependent probe amplification assay), methylation of 24 different TSG was analyzed in 28 MLLmu and MLLwt acute leukemia cell lines. On average, 1.8/24 TSG were methylated in MLLmu AML cells, while 6.2/24 TSG were methylated in MLLwt AML cells. Hypomethylation and expression of the TSG BEX2, IGSF4 and TIMP3 turned out to be characteristic of MLLmu AML cell lines. MLLwt AML cell lines displayed hypermethylated TSG promoters resulting in transcriptional silencing. Demethylating agents and inhibitors of histone deacetylases restored expression of BEX2, IGSF4 and TIMP3, confirming epigenetic silencing of these genes in MLLwt cells. The positive correlation between MLL translocation, TSG hypomethylation and expression suggested that MLL fusion proteins were responsible for dysregulation of TSG expression in MLLmu cells. This concept was supported by our observation that Bex2 mRNA levels in MLL-ENL transgenic mouse cell lines required expression of the MLL fusion gene. Conclusion: These results suggest that the conspicuous expression of the TSG BEX2, IGSF4 and TIMP3 in MLLmu AML cell lines is the consequence of altered epigenetic properties of MLL fusion proteins. © 2009 Röhrs et al; licensee BioMed Central Ltd.